Management of an Uncomplicated Posterior Elbow Dislocation - Blackard, Douglas (1997)
OBJECTIVE: To present a case of an uncomplicated posterior elbow dislocation in a US World Cup athlete and discuss her rehabilitation. BACKGROUND: Traditional protocol for management of this injury has been splint immobilization for several weeks, but research suggests a shortened duration of immobilization and early active motion. DIFFERENTIAL DIAGNOSIS: Elbow dislocation with possible fracture. TREATMENT: The dislocation was reduced and a compression bandage and sling were applied. The sports medicine staff and athlete determined that rehabilitation would involve limited immobilization with a posterior splint. Also, active range-of- motion exercises were to be incorporated early in the range-of- motion program to decrease pain at the articulation. UNIQUENESS: The athlete was not immobilized and her aggressive five-phase rehabilitation program progressed according to decrease in inflammation and increase in range of motion and strength. CONCLUSIONS: Shortened immobilization and return to World Championship competition 6 weeks postinjury had no longterm adverse effects on the athlete.